Supply Chain Risks and Uncertainty in Fresh Agriculture Sector-A Case of Green Onion Supply Chain in Qidong City - Zhang, Zhenzhen (2019)
This research aims to identify the supply chain (SC in short) risks and uncertainty in the fresh agricultural sector and the strategies that can be applied to help participants in the SC to mitigate risks and uncertainty. The case study method is applied in this research, and the approach to progress data collection is through interviews. The case interviewees chosen for interviews are from the green onion SC. From the analysis of data collected, factors that cause SC risks and uncertainty in the case organisations can be identified. Besides, these factors can be categorised to environmental risk and uncertainty, demand risk and uncertainty, supply risk and uncertainty, management and operational risk and uncertainty, financial uncertainty and political and policy uncertainty. The research finds the integrated strategies that can be applied to help to mitigate risks. A new framework is created to help participants in the SC identify risk process.